Inhibition of Escherichia coli Biodegradative Threonine Dehydratase by Pyruvate - Park, Linda S. (1979)
Pyruvate inhibits Escherichia coli K-12 biodegradative threonine dehydratase activity by a mechanism distinct from product inhibition by α-ketobutyrate and catabolite inactivation by intermediary metabolites.